Strategi Pengembangan Pariwisata Berkelanjutan di Desa Samangki Kecamatan Simbang Kabupaten Maros - Rahman, Farid Asfari; Mas Dadang Enjat Munajat; Uud Wahyudin; Reiza D. Dienaputra; Cecep Ucu Rachman (Jurnal Kajian dan Terapan Pariwisata, 2021)
This article aims to formulate a strategic plan for sustainable tourism development in Samangki village, Maros Regency, South Sulawesi. The research design used is descriptive qualitative. At the stage of formulating a sustainable tourism development strategy in Samangki village, using SWOT analysis techniques. The results of the analysis show that Samangki village has internal and external potential for sustainable tourism that can be further developed. Then, potential analysis based on aspects or criteria as the village concept shows that of the seven aspects, only aspects of human resource readiness and aspects of tourism support facilities still need to be improved, while the other five aspects are; tourist attraction, community motivation, facilities and infrastructure, availability and availability of land, in general, are adequate for tourism. In addition, the development of sustainable tourism in Samangka village is quite good, but there is a need for improvement so that in the future Samangka village can become one of the pilot tourism villages in Indonesia.